Ras proteins are essential and selective for the action of insulin-like growth factor 1 late in the G1 phase of the cell cycle in BALB/c murine fibroblasts. - Lu, K (1992)
BALB/c 3T3 cells (A31 cells) require the sequential action of growth factors in order to proliferate from a quiescent growth state. Insulin-like growth factor I (IGF-I) is needed late in the G1 phase of the cell cycle, a time at which expression of the c-Ha-ras protooncogene is near maximal. An anti-ras antibody, introduced by microinjection, specifically blocked the ability of IGF-I to stimulate initiation of DNA synthesis. The antibody was specific for IGF-I; it failed to block serum, platelet-derived growth factor, or epidermal growth factor from inducing c-fos mRNA. By contrast, an anti-G alpha-subunit antibody had no effect on IGF-I-stimulated DNA synthesis but inhibited the induction of c-fos mRNA by platelet-derived growth factor or epidermal growth factor. BPA31 cells are tumorigenic A31-derived cells that progress through G1 in the absence of IGF-I. BPA31 cells produced an autocrine IGF-I that was responsible for the loss of late G1 control; the anti-ras antibody arrested the growth of these cells in late G1. The results suggest that ras proteins are essential for an IGF-I-sensitive, G1 control point.